Weather Data for Citrus Irrigation Management - Larry Parsons; Howard Beck (EDIS)
Weather is one of the most important factors that affects citrus growth and production. Citrus can be grown in a variety of arid and humid climates and can withstand temperatures ranging from 28 to 105°F. However, it performs best in the range between 60° and 86°F. This document is HS950, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Date printed: March 2004.